2020
DOI: 10.1101/2020.03.24.005702
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge synthesis from 100 million biomedical documents augments the deep expression profiling of coronavirus receptors

Abstract: The COVID-19 pandemic demands assimilation of all available biomedical knowledge to decode its mechanisms of pathogenicity and transmission. Despite the recent renaissance in unsupervised neural networks for decoding unstructured natural languages, a platform for the real-time synthesis of the exponentially growing biomedical literature and its comprehensive triangulation with deep omic insights is not available. Here, we present the nferX platform for dynamic inference from over 45 quadrillion possible concep… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Our cross-tissue analysis substantially expands on our 45, 46,58,112 and others' [113][114][115] earlier efforts, allowing us to identify cell subsets across diverse tissues that may be implicated in virus transmission, pathogenesis, or both. Focusing on pathogenesis, in addition to key subsets in the lung, airways and gut, we identified ACE2 + cells that co-express either TMPRSS2 or CTSL in diverse organs, many of which have been associated with severe disease.…”
Section: Discussionmentioning
confidence: 97%
“…Our cross-tissue analysis substantially expands on our 45, 46,58,112 and others' [113][114][115] earlier efforts, allowing us to identify cell subsets across diverse tissues that may be implicated in virus transmission, pathogenesis, or both. Focusing on pathogenesis, in addition to key subsets in the lung, airways and gut, we identified ACE2 + cells that co-express either TMPRSS2 or CTSL in diverse organs, many of which have been associated with severe disease.…”
Section: Discussionmentioning
confidence: 97%
“…17,18 This is supported by research finding a biological mechanism for the SARS-CoV-2 virus to cause olfactory dysfunction. 19,20 Examination of cases and their close contacts in China found a positive association between age and time from symptom onset to recovery. The study also found an association between clinical severity and time from symptom onset to time to recovery.…”
Section: Clinical Featuresmentioning
confidence: 99%
“…Recently, intestinal biopsies of SARS-CoV-2 infected patients clearly show the presence of replicating viruses in epithelial cells of the small and large intestine (Xiao et al, 2020). SARS-CoV-2 infection of the gastrointestinal tract is supported by the fact that ACE2, the virus receptor (Hoffmann et al, 2020), is expressed in intestinal epithelial cells (Zhao et al, 2020) (Lukassen et al, 2020) (Wu et al, 2020a) (Venkatakrishnan et al, 2020) and single cell sequencing analysis suggest that its expression is even higher on intestinal cells compared to lung cells (Xu et al, 2020a).This highlights that SARS-CoV-2 is not restricted to the lung but also infects the gastrointestinal tract. Importantly, many animal coronaviruses are well known to be enteric and are transmitted via the fecal-oral route (Wang and Zhang, 2016).…”
Section: Introductionmentioning
confidence: 99%